2009
DOI: 10.1016/j.otohns.2008.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Laser‐induced hyperthermia for treatment of granulation tissue growth in rats

Abstract: Hyperthermia can significantly inhibit GT growth, with minimal damage to surrounding structures. Our findings suggest a possible role for hyperthermia as a therapeutic model against GT. Further research and long-term studies are needed to explore the utility of laser-induced hyperthermia for inhibition of GT growth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…In contrast to the papers discussed above, Landsberg et al [56] showed beneficial effects of heat on granulation tissue (GT) formation in the rat. In this study, skin was excised first and GT developed in the wound area.…”
Section: Effects Of Heat On Other Tissuesmentioning
confidence: 95%
“…In contrast to the papers discussed above, Landsberg et al [56] showed beneficial effects of heat on granulation tissue (GT) formation in the rat. In this study, skin was excised first and GT developed in the wound area.…”
Section: Effects Of Heat On Other Tissuesmentioning
confidence: 95%
“…Although PTT has been previously reported to successfully treat granulation tissue formation, there is no consensus regarding the optimal temperature for local heating for the treatment of stent-induced granulation tissue formation 11 , 20 , 24 26 . Several studies have reported that at 43 to 65 °C can help inhibit tissue hyperplasia but that an increase to 70 °C induced immediate tissue burn 11 , 19 , 25 . In our current study, stent-induced granulation tissue formation in the rat esophagus was effectively treated with AuNP coated SEMS-mediated local heating at 65 °C, which may effectively burn the granulation tissues generated around the stent.…”
Section: Discussionmentioning
confidence: 99%
“…Although PTT has been previously reported to successfully treat granulation tissue formation, there is no consensus regarding the optimal temperature for local heating for the treatment of stent-induced granulation tissue formation. 11,20,[24][25][26] Several studies have reported that at 43 °C to 65 °C can help inhibit tissue hyperplasia but that an increase to 70 °C induced immediate tissue burn. 11,19,25 In our current study, stent-induced granulation tissue formation in the rat esophagus was effectively treated with AuNP coated SEMS-mediated local heating at 65 °C, which may effectively burn the granulation tissues generated around the stent.…”
Section: Discussionmentioning
confidence: 99%